2019
DOI: 10.1371/journal.pone.0213345
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics, health seeking and delays among new sputum smear positive TB patients identified through active case finding when compared to passive case finding in India

Abstract: BackgroundAxshya SAMVAD is an active tuberculosis (TB) case finding (ACF) strategy under project Axshya (Axshya meaning ‘free of TB’ and SAMVAD meaning ‘conversation’) among marginalized and vulnerable populations in 285 districts of India.ObjectivesTo compare patient characteristics, health seeking, delays in diagnosis and treatment initiation among new sputum smear positive TB patients detected through ACF and passive case finding (PCF) under the national TB programme in marginalized and vulnerable populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 25 publications
2
53
1
Order By: Relevance
“…However, similar to the Myanmar study, the finding in our study allays fears that people with TB detected through ACF could have poor outcomes due to delay in treatment initiation, poor adherence and treatment completion as they are relatively healthier and the diagnosis is not patient-initiated [11]. Additionally, the treatment initiation delays in our cohort of people with TB were not significantly different in the ACF and PCF groups (published elsewhere) [22]. This warrants systematic adherence assessment studies and a qualitative systematic enquiry in India and similar high TB burden countries which can feed into interventions to ensure that early diagnosis through ACF translates into improved outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, similar to the Myanmar study, the finding in our study allays fears that people with TB detected through ACF could have poor outcomes due to delay in treatment initiation, poor adherence and treatment completion as they are relatively healthier and the diagnosis is not patient-initiated [11]. Additionally, the treatment initiation delays in our cohort of people with TB were not significantly different in the ACF and PCF groups (published elsewhere) [22]. This warrants systematic adherence assessment studies and a qualitative systematic enquiry in India and similar high TB burden countries which can feed into interventions to ensure that early diagnosis through ACF translates into improved outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The 'Axshya SAMVAD study' was primarily designed to study the differences in total pre-treatment delay among ACF and PCF-diagnosed people with TB, with a sample size of 325 in each group [20][21][22]. Assessment of the relative difference in TB treatment outcomes was the secondary objective.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Also, the studies have reported ACF to be beneficial in reducing delay in TB diagnosis, out of pocket expenditure, unsuccessful treatment outcomes and incidence of TB [3,7,8]. The benefits of community based ACF activity depends on selection of high risk group, prevalence of the TB in the selected group, incentives provided to healthcare workers, the diagnostic algorithm adopted, and support provided to patients in completing the cascade of TB diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%